Carbon footprint and water footprint assessment of virgin and recycled polyester textiles. Issue 21 (November 2021) - Qian, Weiran; Ji, Xiang; Xu, Pinghua; Wang, Laili
Recycled polyester textile fibers stemming from waste polyester material have been applied in the textile industry in recent years. However, there are few studies focusing on the evaluation and comparison of the environmental impacts caused by the production of virgin polyester textiles and recycled polyester textiles. In this study, the carbon footprint and water footprint of virgin polyester textiles and recycled polyester textiles were calculated and compared. The results showed that the carbon footprint of the virgin polyester textiles production was 119.59 kgCO2 /100 kg. Terephthalic acid production process occupied the largest proportion, accounting for 45.83%, followed by polyester fabric production process, ethylene production process, paraxylene production process, ethylene glycol production process and polyester fiber production process. The total carbon footprint of waste polyester recycling was 1154.15 kgCO2 /100 kg, approximately ten times that of virgin polyester textiles production. As for the water footprint, it showed that virgin polyester fabric production and recycled polyester fabric production both had great impact on water eutrophication and water scarcity. Chemical oxygen demand caused the largest water eutrophication footprint, followed by ammonia-nitrogen and five-day biochemical oxygen demand. The water scarcity footprint of virgin polyester fabric production and recycled polyester fabric production was 5.98 m 3 H2 Oeq /100 kg and 1.90 m 3 H2 Oeq /100 kg, respectively. The comprehensive evaluation of carbon footprint and water footprint with the life cycle assessment polygon method indicated that the polyester fabric production process exhibited greater environmental impacts both for virgin polyester and recycled polyester.